Polyvinyl Alcohol–Borax Slime as Promising Polyelectrolyte for High‐Performance, Easy‐to‐Make Electrochromic Devices. Issue 2 (18th September 2014) - Alesanco, Yolanda; Palenzuela, Jesús; Viñuales, Ana; Cabañero, Germán; Grande, Hans J.; Odriozola, Ibon
Abstract A novel slime‐type electrochromic system based on polyvinyl alcohol (PVA) and borax, in combination with a viologen and a redox pair has been developed. On top of overcoming the limitations of both liquid electrolytes, such as the risk of leakage and difficulty of assembly and of solid electrolytes, such as limited transparency and slow response time, this easy‐to‐make slime electrochromic system offers an excellent wettability and transparency and achieves high‐performance in terms of optical contrast (>65 % at 550 nm), switching time (<5 s as estimated for 90 % of the total transmittance change at 550 nm) and cyclability (8 000–10 000). For the electrochromic devices shown here, the CIELAB 1976 color space coordinates at the "on" state were L*=7.12, a*=18.08, and b*=−21.02, corresponding to a purple color. The color efficiencies were 75.5 cm2 C−1 and 149.3 cm2 C−1 for coloration and bleaching processes respectively.